A Prevalence, Intensity, and Associated of Ectoparasitic Fauna Among Cave-Dwelling Bats from Lombok Island West Nusa Tenggara - Siti Rabiatul Fajri; Sucika Armiani (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
The study aimed to observe the prevalence, intensity, and relationship of ectoparasites in bats in the southern region of Lombok Island, West Nusa Tenggara. The study was conducted in March 2018-February 2019. Bat samples were obtained from four caves in the southern part of Lombok Island. These caves include the Gale-gale Bangkang Cave, Buwun Cave, Semeti Cave, and the Raksasa Cave. Trapping bat samples for identification is done by using the Mist net. While taking ectoparasite samples is done by combing using a toothbrush. The organisms found were collected into sample bottles containing 70% alcohol. Analysis of the relationship between ectoparasites and bats was done by collecting data on ectoparasite species and ectoparasite abundance in each bat species, then further analysis was carried out to find the value of the Similarity Index (IS). The similarity index found is then cluster analysis. Cluster analysis aims to group based on similarity using Euclidean distance. The results of the study stated that based on the examination of 9 species of bats there were 14 species of ectoparasites identified. The value of the highest prevalence of ectoparasites in Gale-gale Cave Bangkang is found in Cyclopodia horsfieldii at 80% with an intensity value of 0.63, in Buwun cave is Amblyomma sp. of 100% with an intensity value of 1.50, in Cave Kenculit is Amblyomma sp. of 40% with an intensity value of 4.25 and in the Raksasa Cave is Cyclopodia horsfieldii of 70% with an intensity value of 0.71. While the relationship between the existence of ectoparasites in the bat's body states that the ectoparasite group in the body of bats can be grouped into 5 community groups. Group I consisted of the ectoparasite community in the Macroglossus minimus, and Rosettus an amplxicaudatus with Euclidean distance of 11,916. Group 2, the ectoparasite community was in Miniopterus pusillus, Rhinopoma microphyllum and Rhinolopus acuminatus with Euclidean distance of 15,362. Group 3 ectoparasite communities in the Chaerephon plicata and Taphozous melanopagon with Euclidean distances of 6,000. Group 4, the ectoparasite community only inhabited Eonycteris spelaea with Euclidean distance of 27,423. And group 5 also only inhabits Rhinolopus simplex with Euclidean distance of 46,293.